Near-Field Radiative Heat Transfer Eigenmodes - Sanders, Stephen; Zundel, Lauren; Kort-Kamp, Wilton J. M.; Dalvit, Diego A. R.; Manjavacas, Alejandro (Physical review letters, 2021)
The near-field electromagnetic interaction between nanoscale objects produces enhanced radiative heat transfer that can greatly surpass the limits established by far-field blackbody radiation. Here, we present a theoretical framework to describe the temporal dynamics of the radiative heat transfer in ensembles of nanostructures, which is based on the use of an eigenmode expansion of the equations that govern this process. Using this formalism, we identify the fundamental principles that determine the thermalization of collections of nanostructures, revealing general but often unintuitive dynamics. Our results provide an elegant and precise approach to efficiently analyze the temporal dynamics of the near-field radiative heat transfer in systems containing a large number of nanoparticles.